Discrimination of plant and animal derived MAG and DAG by principle component analysis of fatty acid composition and thermal profile data - Marikkar, Mohammed Nazrim (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
A study was carried out to distinguish mono- (MAG) and di-acylglycerol (DAG) from plant lipids such as sunflower, rapeseed and soybean oil, from those derived from animal fats such as, lard, goat fat and beef fat using fatty acid and thermal profile data. MAG and DAG of both plant and animal lipids were synthesized according to a chemical glycerolysis method catalyzed by sodium hydroxide. MAG and DAG of individual lipid were isolated and purified using the standard column chromatography method and subjected to fatty acid analysis by gas chromatography (GC) and thermal analysis by differential scanning calorimetry (DSC). The application of principal component analysis (PCA) to the data collected from the individual instrumental technique showed that it was possible to distinctly classify MAG and DAG of plant lipids from those derived from animal fats.